S-conditionally permutable subgroups and p-nilpotency of finite groups - Xu, Y.; Li, X.H. (Український математичний журнал, 2014)
We study the p-nilpotency of a group such that every maximal subgroup of its Sylow p-subgroups is s-conditionally permutable for some prime p. By using the classification of finite simple groups, we get interesting new results and generalize some earlier results. Вивчено p-нільпотентність групи, для якої кожна максимальна підгрупа її силовських p-підгруп є s-умовно переставною для деякого простого p. За допомогою класифiкацiї скінченних простих груп отримано цікаві нові результати та узагальнено деякі результати, що отримані раніше.